2022
DOI: 10.1093/cei/uxac115
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-specific immunotherapy to restore antigen-specific tolerance in Type 1 diabetes and Graves’ disease

Abstract: Type 1 diabetes and Graves’ disease are chronic autoimmune conditions, characterised by a dysregulated immune response. In type 1 diabetes, there is beta cell destruction and subsequent insulin deficiency whereas in Graves’ disease, there is unregulated excessive thyroid hormone production. Both diseases result in significant psychosocial, physiological and emotional burden. There are associated risks of diabetic ketoacidosis and hypoglycaemia in type 1 diabetes and risks of thyrotoxicosis and orbitopathy in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 106 publications
0
5
0
Order By: Relevance
“…GD develops as a result of a dysregulated immunologic reaction against the thyroid gland mediated by antibodies and diminished self-tolerance, but the definite cause of this process is still unknown [2]. Genetic, infectious, immune and environmental factors are all thought to possibly play a role in the disease [3].…”
Section: Text Of Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…GD develops as a result of a dysregulated immunologic reaction against the thyroid gland mediated by antibodies and diminished self-tolerance, but the definite cause of this process is still unknown [2]. Genetic, infectious, immune and environmental factors are all thought to possibly play a role in the disease [3].…”
Section: Text Of Reviewmentioning
confidence: 99%
“…Decreasing the rates of recurrence after remission would also be ideal as this would afford a more definitive 'cure'. Immunosuppressive therapies such as glucocorticoids, azathioprine, and cyclosporin, have been explored in the past but their side effects are limiting [2]. Several immunotherapies are being researched as treatment options for adult GD patients [5].…”
Section: Future Directionsmentioning
confidence: 99%
“…Moreover, individuals with GD have a signi cantly higher risk for other autoimmune diseases, including T1D 18 , rheumatoid arthritis 19 , and systemic lupus erythematosus 20 , than the general population. Previous studies have reported a correlation between GD and T1D 18,21,22 ; however, few studies have examined bidirectional causality. Thus, it is crucial to demonstrate a causal link between GD and T2D.…”
Section: Introductionmentioning
confidence: 99%
“…Potentially less toxic approaches are being considered. Antigen‐specific epitope‐based immunotherapy may lead to restoration of antigen‐specific tolerance 17,18 . Immune checkpoint modulators, 19 chimeric antigen receptor‐based cell therapy, 20 and other novel approaches to disease‐modifying immunotherapy 21 are all being studied and some of these may prove safe and efficacious.…”
mentioning
confidence: 99%
“…Antigen‐specific epitope‐based immunotherapy may lead to restoration of antigen‐specific tolerance. 17 , 18 Immune checkpoint modulators, 19 chimeric antigen receptor‐based cell therapy, 20 and other novel approaches to disease‐modifying immunotherapy 21 are all being studied and some of these may prove safe and efficacious. In our earlier commentary on the use of pro‐proliferative agents for early T1D treatment we noted a preliminary study with the calcium channel‐blocking agent verapamil having the potential to inhibit thioredoxin‐interacting protein, reducing β‐cell glucotoxicity and apoptosis.…”
mentioning
confidence: 99%